2017
DOI: 10.1111/ina.12379
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements and select actinoids in the Canadian House Dust Study

Abstract: Nationally representative baseline data are presented for rare earth elements (REE), thorium (Th) and uranium (U) in house dust sampled from 1025 urban homes, in units of concentrations (μg g ), loadings (μg m ), and loading rates (ng m d ). Spearman rank correlations indicate that, in addition to outdoor sources, consumer products and building materials can influence indoor dust concentrations of REE, Th, and U. Correlations (P<.01) with numbers of occupants, dogs, and cats suggest soil track-in. Correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(116 reference statements)
1
18
0
Order By: Relevance
“…Metals in source media, which are typically measured in mg/kg, contribute to airborne PM through a variety of release, dissipation, resuspension, and combustion processes. Settled house dust has proven to be a sensitive indicator of indoor sources 15 , 87 , 88 and a useful medium for estimating indoor inhalation exposures where sample collection is limited by inadequate resources. 89 , 90 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals in source media, which are typically measured in mg/kg, contribute to airborne PM through a variety of release, dissipation, resuspension, and combustion processes. Settled house dust has proven to be a sensitive indicator of indoor sources 15 , 87 , 88 and a useful medium for estimating indoor inhalation exposures where sample collection is limited by inadequate resources. 89 , 90 …”
Section: Discussionmentioning
confidence: 99%
“…Metals in source media, which are typically measured in mg/ kg, contribute to airborne PM through a variety of release, dissipation, resuspension, and combustion processes. Settled house dust has proven to be a sensitive indicator of indoor sources 15,87,88 and a useful medium for estimating indoor inhalation exposures where sample collection is limited by inadequate resources. 89,90 Strong indoor-outdoor correlations (r > 0.6) for many PM 2.5 elements in the Windsor study homes (Appendix S6) provide evidence of particle infiltration from outdoor sources, but this observation does not necessarily mean an absence of indoor sources (discussed further in Appendix S5).…”
Section: Impact On Source Apportionment Modelsmentioning
confidence: 99%
“…Loading (µg/m 2 ) was judged by the group to be a better indicator of exposure because it combines the dustiness of the indoor environment and the concentration of the compound in dust 8 . Studies with lead have suggested dust loading correlates better with children's blood levels than does the concentration 9,10 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Studies with lead have suggested dust loading correlates better with children's blood levels than does the concentration 9,10 . Its measurement could be achieved with a wipe or with a specific vacuum cleaner, 2,8,11,12 on a measured surface area. One limitation is the spot measurement of loading is influenced by the delay between last cleaning and sampling.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation